FENG SHUI BASED MARKETING: STRATEGI MEMENANGKAN KONSUMEN BERBASIS PEMAHAMAN NILAI-NILAI KEPERCAYAAN TIONGHOA - Albert Kurniawan (Faculty of Economics and Business Universitas Jenderal Soedirman, 2015)
Feng shui is an ancient chinese wisdom about “chi” or positive energy. In reality,most of feng shui’s belief could be explained by modern science. In contemporary practice,feng shui incorporates a wide range of concepts considered to affect a person’s lu ck.These include traditional ideas about feng shui’s five elements, site selection, buildingdesign, as well a belief about certain numbers. Focusing on feng shui’s belief, this paperwill intepret how to utilize feng shui in interest of marketing. Combining marketing mixwith feng shui to attract more attention from the consumers.